Thermal Insulation Materials From Sapropel And Hemp Shives (Cannabis Sativa L .) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
In Latvia, sapropel is an organic lake sediment that is formed from the remains of aquatic animals and aquatic plants, containing mineral particles (sand, clay, calcium carbonate and other compounds). Hemp is a rapidly growing multi – functional energy plant. Hemp seeds and fibre have a very high value on the world market , but in the world when processing hemp, shives of hemp remain as waste. The solution is found in the resources available in Latvia to use them for increasing energy efficiency as a thermal insulation material. The aim of the research is to find out the properties of the thermal conductivity for lightweight concrete from sapropel and hemp shives to be used as a thermal insulation material. An application with the number P-12-200 is submitted to the LR Board of Patents on 20.12.2012. for granting of a patent to the "Hemp shives and sapropel for thermal insulation of buildings”.